Porositas Beton Geopolimer Hybrid Faba Dengan Variasi Modulus Silikat Pada Air Gambut - Ayu Nofikasari; Monita Olivia; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2022)
This study examines the value of porosity in hybrid geopolymer concrete immersed in peat water. FABA as the main ingredient for making concrete has a high silica content. The purpose of this study was to find out the modulus activator with the ratio of modulus silicate (Ms) as one of the factors affecting the porosity value of FABA hybrid geopolymer concrete immersed in peat water. This study has been done to determine the percentage of pores in the concrete by examined the characteristics of the geopolymer concrete material. The mix design of the specimens was determined by a silicate modulus ratio of 2, 2.5, and 3, 12M for the NaOH molarity, 0,65 for Na2SiO3/FABA ratio, and 0,26 for water/FABA ratio. The samples were made in the form of a cylinder concrete with diameter 105 mm and height 105 mm with a total of 24 samples. The samples were cured at room temperature for 28 days and then immersed in peat water for 28 days. The results showed that the lowest geopolymer concrete porosity was found in concrete with Ms 3, which was 11.92% and the highest was found in concrete with Ms 2, which was 14.24%.Keyword : Porosity, fly ash, geopolymer, modulus silicate, NaOH